Image, Function, Meaning, and Structure: The Role of Aphorisms in the Kazakh Epic Poem Kyz Zhibek - Abduov, Muhammadgali; Abduova, Nazilya; Stanciu, Nicolae (Studia mythologica Slavica, 2020)
In this article, the function of aphorisms in folk song, which also contains lyrical and dramatic elements, is analysed and defined through cultural (mostly folklore) literature, and linguistic methods. The main purpose of this paper is to show the role of the gnomic words generated by folk creators in an epic poem’s plot, their main functions in the development of conflict and the aesthetic expression of the work. Therefore, the meaning of symbols has been interpreted in close connection with the actions, archetypes and metaphors inserted in the structure of the song. Using as an example the song “Kyz Zhybek”, which is a prominent creation in Kazakh folklore, and reviewing research papers on the subject, the present article follows the contrastive analysis in researching the echoes of archetypal traditions in a Muslim cultural frame. Ethnos in culture remains in an attempt to recover the identity of a group using what seems specific in folklore, history, and linguistics and to track them in an original ideology articulated on national and universal bases. This paper may help researchers when studying folklore heritage, with understanding the scope of using the aphorisms and the main function actualised by them in folk literature. In addition, the role of aphorisms in a folk song is systematised, and their historical and identity significance is underlined.